Understanding the Role of Clinical Champions and Their Impact on Clinician Behavior Change: The Need for Causal Pathway Mechanisms - Morena, Alexandra L.; Gaias, Larissa M.; Larkin, Celine (Frontiers in Health Services, 2022)
Abstract Background: The clinical champion approach is a highly utilized implementation strategy used to mitigate barriers and improve outcomes of implementation efforts. Clinical champions are particularly effective at addressing provider-level barriers and promoting provider-behavior change. Yet, the specific causal pathways that explain how clinical champions impact provider behavior change have not been well-explicated. The current paper applies behavior change models to develop potential causal pathway mechanisms. Methods: The proposed mechanisms are informed by previous literature involving clinical champions and empirically supported behavior change models. These models are applied to link specific attributes to different stages of behavior change and barriers for providers. Results: Two unique pathway mechanisms were developed, one that explicates how providers develop intention to use EBPs, while the other explicates how providers transition to EBP use and sustainment. Clinical champions may promote intention development through behavioral modeling and peer buy-in. In contrast, champions promote behavioral enactment through skill building and peer mentorship. Conclusion: Clinical champions likely play a critical role in reducing provider implementation barriers for providers across various phases of behavior change. The proposed pathways provide potential explanations for how clinical champions promote provider behavior change. Future research should prioritize empirically testing causal pathway mechanisms.